Transcription analysis of an immune factor in a main African malaria vector Anopheles funestus - Ramashia, Witness (My University, 2022)
Anopheles funestus s.s. is one of the vectors that plays a major role in the transmission of malaria in sub-Saharan Africa, with Plasmodium falciparum the principal human malaria parasite, responsible for the majority of cases in Africa. Transmission of the malaria parasite to the human host depends on the successful completion of the parasite’s sexual development in the Anopheles vector, however, the mosquito’s immune system influences the plasmodial transmission cycle. The defensive immune response of the Anopheles contributes to decrease parasite numbers, but, certain factors in the immune response and blood meal favour infection. Anopheles C-type lectins (CTLs) are immune protein recognition receptors involved in the melanization process, the insect’s prime immune reaction. CTLs, particularly An. gambiae CTL4 has been shown to inhibit melanization, thereby supporting the survival of ookinetes to oocysts and increasing the potential risk of infection. In this study, An. funestus s.s. CTL4 gene was successfully amplified and the analyzed protein was identified to consist of an N-terminal tri-cysteine (CXCPC) motif and one CTL domain with two calcium ions binding sites. Structural modelling revealed that this CTL4 domain is composed of two αhelices, five β-sheets and double-loop fold that are stabilized by two highly conserved disulphide bridges. In order to obtain sufficient number of fed adult females for infection/treatment studies, optimization of the feeding rate using an artificial feeding system was determined. Adult females provided with distilled water (dH2O), 72 hours prior to blood feeding had an increased feeding rate (p = 0.0117), whereas the age at which adult females received their first blood meal had no impact on the feeding success rate. However, the cumulative probability of survival post blood feeding is affected by the age of the mosquitoes and reached 82, 66 and 50% at ages 5, 10 and 15 days old, respectively. Successful ingestion of infected P. falciparum (NF54 strain) blood by the laboratory An. funestus s.s. colony with was confirmed by the presence of the parasites’ circumsporozoite protein (CPS) gene amplification. The mRNA expression level of the CTL4 in P. falciparum infected and uninfected mosquitoes were not significantly different (p = 0.2560). Sensitivity of An. funestus s.s. to antimalarial drug chloroquine (CQ) displayed no larvicidal activity, whereas CQ in the blood meal knocked down and killed Anopheles adults in a dose-dependent manner. Collectively, these observations show that it is feasible to obtain P. falciparum infected laboratory An. funestus s.s. using an artificial membrane feeding system. This can be used for comprehensive study on natural Plasmodium-Anopheles interactions that may provide novel malaria control strategies’ including transmission-blocking vaccines. In addition, this study suggests that CQ interferes with the Anopheles immune system, compromising the defensive response. This highlights the importance of understanding the impact that antimalarial drugs have on malaria parasite transmission in the Anopheles vector.
A research report submitted in fulfilment of the requirements for the degree of Master of Science in Medicine (Virology) to the Faculty of Health Science, School of Pathology, University of the Witwatersrand, Johannesburg, 2022